2013
DOI: 10.1002/gea.21441
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Site Formation History and Potential Disturbance of Stratigraphic Context in Vertisols at the Debra L. Friedkin Archaeological Site in Central Texas, USA

Abstract: Archaeological sites within physically “active” soils, such as Vertisols, are considered suspect by archaeologists because of concern for possible disturbance of stratigraphic context. Pedology, micromorphology, and geochemistry are tools useful for assessing soil mixing. Clay‐rich floodplain soils (Typic Haplusterts) were examined at the Debra L. Friedkin archaeological site along Buttermilk Creek in southwestern Bell County, Texas, USA. The soil contains abundant lithic (mainly chert) artifacts and was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Downprofile variations of these data lack the erratic changes indicative of multiple unrelated generations of soil formation, suggesting that each paleosol more or less represents a single episode of pedogenesis. These data also lend support to the building consensus that the pedoturbation “inverting” model is inadequate to explain the developmental mechanics for all Vertisols (Driese et al, ; Lindquist et al, ; Nordt et al, ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Downprofile variations of these data lack the erratic changes indicative of multiple unrelated generations of soil formation, suggesting that each paleosol more or less represents a single episode of pedogenesis. These data also lend support to the building consensus that the pedoturbation “inverting” model is inadequate to explain the developmental mechanics for all Vertisols (Driese et al, ; Lindquist et al, ; Nordt et al, ).…”
Section: Discussionsupporting
confidence: 71%
“…Each paleosol is interpreted to represent a single phase of soil development without significant reworking of the substrate by Vertisols processes, which may cause irregular downprofile changes to magnetic and DRS data, resulting in a more ambiguous signal. The data do not provide evidence of strong mixing by pedoturbation, adding to a growing consensus that the “inversion” model does not adequately explain all Vertisol formation (Driese et al, ; Nordt et al, ). However, it should be noted that mixing and stratigraphic inversions may occur near the margins of gilgai topography and synclines (Kovda et al, ).…”
Section: Resultsmentioning
confidence: 68%
“…Morrow et al (2012) have suggested that decreasing artifact densities with depth demonstrates downward drift. Multiple lines of evidence refute this hypothesis (Driese et al 2013; Jennings 2012a; Keene 2009;Lindquist et al 2011 ;Waters, Forman, et al 2011). If the smallest particles in the matrix (e.g., clays, sands, carbonates) are not mixed, and diagnostic artifacts are not mixed, and OSL ages exhibit no significant reversals, it is highly unlikely that the artifact assemblage is mixed.…”
Section: Discussionmentioning
confidence: 98%
“…Our pa-per should not be considered a response or rebuttal to Morrow et al's (2012) paper. Their concerns with site context and dating have been addressed in more detail elsewhere (Driese et al 2013; Jennings 2012a; Keene 2009;Lindquist et al 2011) and are not further considered here. However, our paper does address their second argument-that the BCC artifacts are indistinguishable from Clovis and that the BCC assemblage simply represents an "early" Clovis occupation.…”
mentioning
confidence: 99%
“…As a conservative estimate, Waters et al [68] place the age of the Buttermilk Creek Complex as ca. 15,500-13,200 years ago (see [123] for a conflicting opinion on dates and context; see [124,125] for rebuttals). Gault (Figure 4) is located approximately 250 m upstream from Debra L. Friedkin.…”
Section: Earlier Techno-complexesmentioning
confidence: 99%